A radical coupling reaction of DMSO with sodium arylsulfinates in air : mild utilization of DMSO as C1 resource for the synthesis of arylsulfonyl dibromomethane. Issue 31 (8th March 2016) - Shi, Jie; Tang, Xiao-Dong; Wu, Yan-Cheng; Fang, Jie-Fang; Cao, Liang; Chen, Xiao-Yun; Wang, Zhao-Yang
Abstract : A radical coupling reaction of DMSO with ArSO2 Na without the needs of anaerobic atmosphere to afford ArSO2 CHBr2 is described. Abstract : A radical coupling reaction of DMSO with sodium arylsulfinates under air atmosphere to afford arylsulfonyl dibromomethane is described. This transformation provides a novel approach for the utilization of DMSO as a C 1 resource with mild temperature without the need for an anaerobic atmosphere.